2004
DOI: 10.1177/004947550403400302
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Artesunate following Oral and Rectal Administration in Healthy Sudanese Volunteers

Abstract: The aims of this study were to determine the pharmacokinetic parameters of a single dose of 200 mg oral and rectal artesunate in healthy volunteers, and to suggest a rational dosage regimen for rectal administration. The study design was a randomized open cross-over study of 12 healthy volunteers; the analytical method used was a reversed phase high performance liquid chromatography with post column derivatization and subsequent ultraviolet detection. Pharmacokinetic parameters were derived from the main metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…Artesunate is presumed to undergo marked first-pass effect; thus, the variability might be caused by differences in the extent of the enzyme activity among persons. 15 After AS alone or in combination with SP, it has also been observed that the C max and AUC values of DHA, in the present study, exceeded that of AS (Tables 1 and 2). …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Artesunate is presumed to undergo marked first-pass effect; thus, the variability might be caused by differences in the extent of the enzyme activity among persons. 15 After AS alone or in combination with SP, it has also been observed that the C max and AUC values of DHA, in the present study, exceeded that of AS (Tables 1 and 2). …”
Section: Discussionsupporting
confidence: 62%
“…13 Previously, the main methods for their quantification were electrochemical detection with detection limits of approximately 10 ng/mL by using sample volumes of approximately 0.5-1 mL plasma or post-column derivatization with methanolic alkali and subsequent ultraviolet detection with limits of detection of approximately 30 ng/mL. [14][15][16][17][18][19][20] Currently, the suitable method for quantification of these compounds in plasma is liquid chromatography coupled with mass spectrometry detection (LC-Ms or LC-MS/MS) with quantification limits of approximately 1 ng/mL using only 50-μL plasma sample volumes. [21][22][23][24][25] However, some of the problems encountered the latter bioanalytical methods include lack of appropriate stable isotope-labeled AS and DHA internal standards, in addition to expensive solid phase extraction cartridges that most commonly used for extraction of AS and DHA from biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Using pharmacokinetic data from healthy volunteers, an appropriate dose of artesunate was selected for administration per rectum that would be expected to provide blood levels of dihydroartemesinin above the minimum inhibitory concentration that eliminates 90% of the parasites (MIC 90 ) for 5.3 ± 2.1 hours. 10 The rapid parasite clearance and deffervescence of fever in all 99 patients confirms the dosing schedule in this group of patients was entirely appropriate. The parasitemia and fever clearance times in this study were significantly shorter than that reported by Looareesuwan et al 11,12 and Thwe et al 13 but not significantly different from that reported by Eduardo and Gomez 14 and Bhatt et al 15 The choice of second agent was made based on available data of mefloquine from Southeast Asia and cost because pyrimethamine/sulfadoxine and doxycycline are inexpensive and widely available.…”
Section: Discussionmentioning
confidence: 57%
“…Group C (30 patients): Mefloquine tablets (total dose, 15 mg/kg body weight), split in 2 equal doses 24 hours apart, started 12 hours after the last dose of artesunate A pharmacokinetic study of oral and rectally administered artesunate in Sudanese healthy volunteers was used to devise the suggested dosage regimen of rectal artesunate, 200-mg rectocaps every 8 hours. 10 Patients were laid in a left lateral position, and an artesunate rectocap was inserted into the rectum beyond the anal verge by a trained nurse. The patients were confined to bed for at least 1 hour after the insertion; if the rectocap was expelled within 1 hour of administration, another dose was inserted.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation